The Islamic Moral Perspective on Semiotic Analysis of Reyog Art against Children's Drama "Songgolangit Sayemboro" - Marjuni Misri Marjuni; Adly Rosyad Fudhulul Ulwani (Islamika Inside: Jurnal Keislaman dan Humaniora, 2022)
Abstract: The semiotic interpretation of Reyog as an intangible cultural treasure and a representation of Ponorogo people's historical knowledge is still debatable, especially in light of Reyog Ponorogo's failure to become one of the nominees to be presented to UNESCO in the second week of April 2022. This research explains how a) Reyog Ponorogo as a local culture requires socio-religious values and b) the historical construction of Reyog Ponorogo has strengthened the reality of social change. Child Reog Performance and Drama "Songgolangit Sayemboroo" on December 11, 2021, on the Youtube Channel of the East Java Pavilion, Taman Mini Indonesia Indah was studied (TMII). This qualitative research uses a constructivist method. Roland Barthes' semiotic analysis identifies denotation, connotation, and myth in Child Reog and Songgolangit Sayemboroo. The study found that a. structured denotation relates to valued artwork. Reyog Ponorogo, drums, demung, saron, Peking, trumpet, gong, kempul, bonang, slenthem, gender, xylophone, violin, zither, and angklung are cultural values. The Child Reog Show and Drama "Songgolangit Sayemboroo" are put on because of how history was made to seem. Construction interpretation is a myth that isn't necessarily about mythology. The online presentation shows that the social reconstruction of Ponorogo has lasted a long time in the form of a vernacular building in the Reyog Ponorogo style which requires historical values ​​which are very important for cultural development. Reyog's art and dance performances are part of Ponorogo's history to preserve art, culture, and noble legacy and promote equal rights for women. In a family-run government, human rights breaches and gender inequalities may occur. Reyog mentioned a critical lesson in the Quran Chapter 51 verse 56 and Chapter 4 verse 36 about a wonderful lady's spiritual effort to love God without damaging or hurting others, let alone both parents' hearts.